Literasi Digital dan Sosial Emosional untuk Meningkatkan Pengetahuan Pelajar SMA Mengenai Radikalisme Beragama - Mashuri, Ali; Nurmala, Sukma (Jurnal Pengabdian UNDIKMA, 2024)
This community service program aims to enhance digital and emotional social literacy of high school students to prevent them from being easily exposed to religious radicalism. The method of the community service program takes shape via interactive socialization about cognitive and social-emotional digital literacies as an antidote to extremist ideology involving 64 students at SMA Brawijaya Smart School, Malang City. The service evaluation instrument consists of a pre-test and post-test, which are then analyzed inferentially using the Wilcoxon Signed-Rank Test. The results of the socialization showed that the levels of participants’ understanding of radicalism in general, religious radicalism in particular, and cognitive and social-emotional digital literacies were significantly higher at the post-test stage compared to the pre-test stage. The final findings showed that participants positively evaluated the goal, implementation, and outcome from the socialization. Moreover, participants rated that socialization could meet their needs to know more about radicalism in general, religious radicalism in particular, and the cognitive and social-emotional digital literacies to tackle religious extremist ideology.